The derivative of y = `(e^(5u) - e^(-5u))/(e^(5u) + e^(-5u))` has to be determined.

`dy/(du)` = `((5*e^(5u) + 5*e^(-5u))*(e^(5u) + e^(-5u)) - (e^(5u) - e^(-5u))*(5e^(5u) - 5e^(-5u)))/(e^(5u) + e^(-5u))^2`

=> `dy/(du)` = `(5*(e^(10u) + e^(-10u) + 2) - 5*(e^(10u) + e^(-10u) - 2))/(e^(5u) + e^(-5u))^2`

=> `dy/(du) ` = `(5*4)/(e^(5u)...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

The derivative of y = `(e^(5u) - e^(-5u))/(e^(5u) + e^(-5u))` has to be determined.

`dy/(du)` = `((5*e^(5u) + 5*e^(-5u))*(e^(5u) + e^(-5u)) - (e^(5u) - e^(-5u))*(5e^(5u) - 5e^(-5u)))/(e^(5u) + e^(-5u))^2`

=> `dy/(du)` = `(5*(e^(10u) + e^(-10u) + 2) - 5*(e^(10u) + e^(-10u) - 2))/(e^(5u) + e^(-5u))^2`

=> `dy/(du) ` = `(5*4)/(e^(5u) + e^(-5u))^2`

=> `dy/(du) ` = `20/(e^(5u) + e^(-5u))^2`

**The derivative of y = `(e^(5u) - e^(-5u))/(e^(5u) + e^(-5u))` is `dy/(du)` = `20/(e^(5u) + e^(-5u))^2` **